Alternative control to black spot disease in papaya genotypes - Santos,Pedro Henrique Dias dos (2017)
ABSTRACT To find control forms alternative to fungicides, this study aimed to evaluate the effect of products with potential to control black spot (Asperisporium caricae) in different papaya genotypes. Installed in a greenhouse, the experiment was conducted in randomized blocks (RB) with factorial arrangement 5x6, three replicates, and spraying of four products (Bion®, Bordeaux mixture, Ecolife®, and Bordasul®) in six papaya genotypes (‘Sunrise Solo PT’, ‘STZ 03’, ‘Golden’, ‘Tailândia’, ‘Maradol’ and ‘UENF-CALIMAN 01’), while control was sprayed only with water. The severity (BSS) and the incidence (BSI) of black spot on the leaves were quantified, as well as the area under the disease progress curve (AUDPC). There was variability among the evaluated genotypes, highlighting ‘STZ 03’, ‘Maradol’ and ‘UENF/CALIMAN 01’ as the most resistant genotypes. ‘Tailândia’ (susceptible) showed greater response to the products. Plants sprayed with Bion®, Bordeaux mixture and Bordasul® had reduced black spot means.